Photovoltaic Solar Energy Systems: Market Trends In The United States - Joshua Krautmann; Jinwen Zhu (Institute of Advanced Engineering and Science, 2012)
The world today uses more energy than ever before. As a global society we must find more renewable and efficient sources to obtain our energy. One of these sources might come in the form of something that we interact with everyday, the sun. Photovoltaic solar cells are a growing market in the renewable energy sector. Basic PV cell materials are discussed and the PV market in the United States is analyzed; are PV solar energy systems the answer to our current and future energy needs?